Pengelolaan PENGELOLAAN REPUTASI PT TIKI JALUR NUGRAHA EKAKURIR (JNE) DALAM KASUS PENGIRIMAN BARANG YANG LAMA - Maulida, Ade (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
In recent years PT Tiki Jalur Nugraha Ekakurir (JNE) has received a lot of complaints from its customers regarding the very long delivery of goods, this incident has led to negative reviews from other JNE customers on various online media platforms, therefore the goal from this research to find out or find the reputation of the JNE company through the company based on complaints or complaints from its consumers on various online media platforms, based on the elements of Online Reputation Management, including Review Sites, Blog Posts, Social Media, Forums, Competitors. Websites and Press Releases, through the theories and concepts of reputation and Issues Management. This writing was compiled by observing through the news on various online media platforms. In responding to the news, JNE responded with positive things, namely by providing an explanation of the problem and also providing facilities for submitting complaints or asking questions about JNE and making various efforts such as showing various kinds of CSR, Campaigns, Positive Programs on Social Media. . The efforts made by JNE are by always showing the company's commitment and social responsibility, being able to understand customers so as not to make negative complaints, which of course if these negative complaints are continuously made can damage the reputation of JNE itself. Keywords : Reputation, Online Reputation Management, Issue Management, PT Tiki Jalur Nugraha Ekakurir (JNE)